2014
DOI: 10.1038/ncomms5884
|View full text |Cite
|
Sign up to set email alerts
|

RNase ZS1 processes UbL40 mRNAs and controls thermosensitive genic male sterility in rice

Abstract: Thermosensitive genic male-sterile (TGMS) lines, which are male-sterile at restrictive (high) temperatures but male-fertile at permissive (low) temperatures, have been widely used in breeding two-line hybrid rice (Oryza sativa L.). Here we find that mutation of thermosensitive genic male sterile 5 (tms5) in rice causes the TGMS trait through a loss of RNase Z S1 function. We show that RNase Z S1 processes the mRNAs of three ubiquitin fusion ribosomal protein L40 (Ub L40 ) genes into multiple fragments in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
182
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(203 citation statements)
references
References 47 publications
6
182
1
6
Order By: Relevance
“…Photoperiod-sensitive and thermo-sensitive lines are the two major types of rice PTGMS germplasm resources (5)(6)(7)(8). Two widely used PTGMS genes have been cloned: one is a noncoding RNA gene (6,7), and the other codes for RNase Z S1 (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoperiod-sensitive and thermo-sensitive lines are the two major types of rice PTGMS germplasm resources (5)(6)(7)(8). Two widely used PTGMS genes have been cloned: one is a noncoding RNA gene (6,7), and the other codes for RNase Z S1 (8).…”
mentioning
confidence: 99%
“…Two widely used PTGMS genes have been cloned: one is a noncoding RNA gene (6,7), and the other codes for RNase Z S1 (8). The male fertility of PTGMS lines is reversible in response to environmental conditions, which enables the PTGMS lines to propagate via selfpollination under environmental conditions restoring the male fertility and to outcross with restorer lines for hybrid seed production under conditions suppressing male fertility (5)(6)(7)(8). Because PTGMS traits are controlled by nuclear recessive genes and male fertility can be restored by any normal rice cultivars (5-8), broader genetic resources can be explored for strong heterosis (1,5).…”
mentioning
confidence: 99%
“…Recently, a joint research team led by Chuxiong Zhuang of South China Agricultural University and Xiaofeng Cao of Institute of Genetics and Development Biology, Chinese Academy of Sciences published their work on the cloning and molecular characterization of the gene thermosensitive genic male sterile 5 (tms5) in rice in Nature Communications [1]. This is the result of a long-term collaboration representing an important advance in male sterility research in crops.…”
mentioning
confidence: 99%
“…These RNases generally participate in the 3Ј processing of tRNA precursors lacking an encoded CCA sequence, cleaving right after the discriminator nucleotide to generate a substrate for CCA addition by tRNA nucleotidyltransferase (1). In addition to tRNA precursors, some mRNAs have also been identified as substrates including some in rice (2) and Escherichia coli (3), raising the possibility of other putative substrates (4). This is of particular significance in E. coli, because the precursors of all 86 tRNAs already contain the CCA trinucleotide (5), obviating a need for the action of RNase Z.…”
mentioning
confidence: 99%
“…Ribonucleases play an important role in cellular RNA metabolism, and recent studies have revealed that these enzymes may act as important regulators of small RNAs (sRNAs) 2 by participating in their maturation or turnover (12,13). 6S RNA, a stable sRNA, is an important transcription regulator that acts by binding to the sigma 70-containing holoenzyme of RNA polymerase (E 70 ) and reducing its activity (14).…”
mentioning
confidence: 99%